UUM celebrates 46th ASEAN Day - Shazwani, Ili (New Straits Times, 2013)
IT was a beehive of activity at Dewan Mu'adzam Shah at Universiti Utara Malaysia (UUM) in Sintok here with some 300 students from the public and private higher learning institutions in the northern region states taking part in the 46th Association of Southeast Asian Nations (Asean) Day celebration.